Emerging Role of [18F]FLT PET/CT in Lymphoid Malignancies: A Review of Clinical Results - Anna Giulia Nappi; Giulia Santo; Lorenzo Jonghi-Lavarini; Alberto Miceli; Achille Lazzarato; Flavia La Torre; Francesco Dondi; Joana Gorica (Hematology Reports, 2024)
Fluorine-18 fluorodeoxyglucose ([18F]FDG) is nowadays the leading positron emission tomography (PET) tracer for routine clinical work-ups in hematological malignancies; however, it is limited by false positive findings. Notably, false positives can occur in inflammatory and infective cases or in necrotic tumors that are infiltrated by macrophages and other inflammatory cells. In this context, 3′-deoxy-3′-[18F]fluorothymidine ([18F]FLT) has been shown to be a promising imaging biomarker of hematological malignant cell proliferation. In this review, a total of 15 papers were reviewed to collect literature data regarding the clinical application of [18F]FLT PET/CT in hematological malignancies. This imaging modality seems to be a suitable tool for noninvasive assessment of tumor grading, also showing a correlation with Ki-67 immunostaining. Moreover, [18F]FLT PET/CT demonstrated high sensitivity in detecting aggressive lymphoma lesions, especially when applying a standardized uptake value (SUV) cutoff of 3. At baseline, the potential of [18F]FLT imaging as a predictive tool is demonstrated by the low tracer uptake in patients with a complete response. However, its use is limited in evaluating bone diseases due to its high physiological uptake in bone marrow. Interim [18F]FLT PET/CT (iFLT) has the potential to identify high-risk patients with greater precision than [18F]FDG PET/CT, optimizing risk-adapted therapy strategies. Moreover, [18F]FLT uptake showed a greater ability to differentiate tumor from inflammation compared to [18F]FDG, allowing the reduction of false-positive findings and making the first one a more selective tracer. Finally, FLT emerges as a superior independent predictor of PFS and OS compared to FDG and ensures a reliable early response assessment with greater accuracy and predictive value.